PENGGUNAAN MEDIA KOMIK STRIP DALAM MENINGKATKAN KETERAMPILAN MENULIS TEKS ANEKDOT DI SMK NEGERI 1 SUMEDANG - Lilis Mulyati (Riksa Bahasa, 2016)
This study aimed to: 1) the student's motivation after media usage comic strip in improving writing skills anecdotal text. 2) the extent to which improving student learning outcomes after a scientific approach to the comic strip medium is applied. Observation held for two cycles, with research instruments student worksheets, student activity observation sheets and questionnaires. The results showed 1) the students' motivation increased after the implementation of the scientific approach to media comic strip. 2) increased student learning outcomes, which is marked by the acquisition value of completeness learning, the first cycle of 65% to 80% in the second cycle. This shows that the scientific approach to the medium of the comic strip is increasing motivation and learning outcomes of students in writing the text of anecdotes.Keywords: scientific approach, media comic strip